3D bioprinting of heterogeneous tissue-engineered skin containing human dermal fibroblasts and keratinocytes. (10th February 2023) - Li, Meng; Sun, Lei; Liu, Zixian; Shen, Zhizhong; Cao, Yanyan; Han, Lu; Sang, Shengbo; Wang, Jianming
Abstract : Three-dimensional (3D) printed skin substitutes have great potential for wound healing. Abstract : Three-dimensional (3D) printed skin substitutes have great potential for wound healing. However, current 3D printed skin models are limited in simulating heterogeneity and complexity of skin tissue due to the lack of customized bioinks optimized for different skin layers. Herein, different gelatin methacrylate (GelMA)/nano-cellulose (BNC) bioink formulations were used to develop heterogeneous tissue-engineered skin (HTS) containing layers of fibroblast networks with larger pores, basal layers with smaller pores, and multilayered keratinocytes. The results revealed that the 10%GelMA/0.3%BNC bioink was better to model bioprinted dermis due to its high printability and cell-friendly sparse microenvironment. Additionally, the 10%GelMA/1.5%BNC bioink as the basal layer presented a dense network and sufficient material stiffness to support the establishment of keratinocyte confluent monolayers. The HTS not only had the ability to remodel the extracellular matrix but also supported epidermis reconstruction and stratification in vitro, with the epidermal thickness growing to 80 μm after 14 days. Furthermore, the full-thickness wound healing experiments demonstrated that the HTS promoted granulation tissue regeneration and improved wound healing quality. The generated skin of the HTS group had hair follicles and early-stage rete ridge structures, which were similar to normal skin in vivo . The HTS may deliver effective skin grafts for future clinical treatments.